Up to a Limit? Privacy Concerns of Bystanders and Their Willingness to Share Additional Information with Visually Impaired Users of Assistive Technologies - Ahmed, Tousif; Kapadia, Apu; Potluri, Venkatesh; Swaminathan, Manohar (Proceedings of the ACM on Interactive, Mobile, Wearable, and Ubiquitous Computing, 2018)
The emergence of augmented reality and computer vision based tools offer new opportunities to visually impaired persons (VIPs). Solutions that help VIPs in social interactions by providing information (age, gender, attire, expressions etc.) about people in the vicinity are becoming available. Although such assistive technologies are already collecting and sharing such information with VIPs, the views, perceptions, and preferences of sighted bystanders about such information sharing remain unexplored. Although bystanders may be willing to share more information for assistive uses it remains to be explored to what degree bystanders are willing to share various kinds of information and what might encourage additional sharing of information based on the contextual needs of VIPs. In this paper we describe the first empirical study of information sharing preferences of sighted bystanders of assistive devices. We conducted a survey based study using a contextual method of inquiry with 62 participants followed by nine semi-structured interviews to shed more insight on our key quantitative findings. We find that bystanders are more willing to share some kinds of personal information with VIPs and are willing to share additional information if higher security assurances can be made by improving their control over how their information is shared.